Stuttering - Aslihan Okan Ibiloglu (Psikiyatride Güncel Yaklaşımlar, 2011)
Stuttering is a multi-dimensional problem involving a particular kind of speech behavior, feelings, beliefs, self- concepts, and social interactions. Stutterers have "good days"? with less stuttering? and "bad days"? when they can't get a word out. Current research suggests that it is caused by a complex interaction between a person’s physical makeup and the environment. Stutterers are, on average, psychologically normal, except for fears and anxieties around talking. Stress and anxiety may aggravate stuttering. On the other hand, most stutterers speak fluently when relaxed, but stutter under stress. Stuttering affects people from all levels of the socioeconomic scale and is found in all parts of the world. The frequency of stuttered words, the type of speech disruption, and the presence of, and type of associated behavior varies from person to person. In terms of prognosis, early detection is important. The aim of this article, is to examine the persons who stutter, within the light of the etiology, frequency, definition, differential diagnosis, and comorbid psychiatric symptoms.